Efavirenz reduces renal excretion of lamivudine in rats by inhibiting organic cation transporters (OCT, Oct) and multidrug and toxin extrusion proteins (MATE, Mate) - Ceckova, Martina; Reznicek, Josef; Deutsch, Birgit; Fromm, Martin F; Staud, Frantisek (PloS one, 2018)
Efavirenz (EFV) is a non-nucleoside reverse transcriptase inhibitor used in first-line combination antiretroviral therapy (cART). It is usually administered with nucleoside reverse transcriptase inhibitors (NRTI), many of which are substrates of OCT uptake solute carriers (SLC22A) and MATE (SLC47A), P-gp (MDR1, ABCB1), BCRP (ABCG2), or MRP2 (ABCC2) efflux transporters. The aim of this study was to evaluate the inhibitory potential of efavirenz towards these transporters and investigate its effects on the pharmacokinetics and tissue distribution of a known Oct/Mate substrate, lamivudine, in rats. Accumulation and transport assays showed that efavirenz inhibits the uptake of metformin by OCT1-, OCT2- and MATE1-expressing MDCK cells and reduces transcellular transport of lamivudine across OCT1/OCT2- and MATE1-expressing MDCK monolayers. Only negligible inhibition of MATE2-K was observed in HEK-MATE2-K cells. Efavirenz also reduced the efflux of calcein from MDCK-MRP2 cells, but had a rather weak inhibitory effect on Hoechst 33342 accumulation in MDCK-MDR1 and MDCK-BCRP cells. An in vivo pharmacokinetic interaction study in male Wistar rats revealed that intravenous injection of efavirenz or the control Oct/Mate inhibitor cimetidine significantly reduced the recovery of lamivudine in urine and greatly increased lamivudine retention in the renal tissue. Co-administration with efavirenz or cimetidine also increased the AUC0-∞ value and reduced total body clearance of lamivudine. These data suggest that efavirenz is a potent inhibitor of OCT/Oct and MATE/Mate transporters. Consequently, it can engage in drug-drug interactions that reduce renal excretion of co-administered substrates and enhance their retention in the kidneys, potentially compromising therapeutic safety.
Keywords: alkyny; Lamivudine; Madin Darby Canine Kidney Cells; Rats; lamivudin; psi; protein spojený s mnohočetnou rezistencí k lékům 2; HEK293 Cells; metformin; Cyclopropanes; Dogs; ROC Curve; proteiny přenášející organické kationty; Rats, Wistar; plocha pod křivkou; mužské pohlaví; Multidrug Resistance-Associated Protein 2; Organic Cation Transport Proteins; proteiny spojené s mnohočetnou rezistencí k lékům; benzoxaziny; ROC křivka; buňky MDCK; krysa rodu Rattus; inhibitory reverzní transkriptasy; poločas; Benzoxazines; zvířata; HEK293 buňky; Humans; cimetidin; Multidrug Resistance-Associated Proteins; ledviny; eliminace ledvinami; Half-Life; Reverse Transcriptase Inhibitors; Area Under Curve; Alkynes; cyklopropany; Cimetidine; potkani Wistar; Kidney; Renal Elimination; Metformin; lidé; Male; Animals